EXPLORING GAPS IN THE APPOINTMENT AND ORGANIZATION OF FORENSIC COMMODITY EXAMINATIONS - E. Makhnin (Теория и практика судебной экспертизы, 2014)
The author examines possibilities for reducing the timeframe of forensic vehicleevaluation (specialization 13.4) in civil and criminal cases using examples from relevantRFCFS laboratory casework.